The effect of T-stress on mixed mode I/II fracture of composite materials: Reinforcement isotropic solid model in combination with maximum shear stress theory. (15th October 2021) - Fakoor, Mahdi; Shahsavar, Sadra
Highlights: RIS-MSS for mixed mode I/II fracture investigation of cracked orthotropic materials. Maximum shear stress criterion in combination with RIS concept. Cracks are assumed to be oriented along and across the fibers. The effect of T-stress term on crack propagation of off-axis cracks is investigated. RIS-MSS criterion is applicable for both cracks oriented along and across the fibers. Abstract: Due to the existence of cracks and defects in composite materials during the manufacturing process, damage and crack growth in these materials must be anticipated before application. In the present research, an efficient theoretical mixed mode I/II fracture criterion is proposed for fracture investigation of orthotropic materials considering the effects of non-singular stress term in William's series expansion. This criterion is developed combining the maximum shear stress (MSS) theory with reinforcement isotropic solid concept (RIS) as a superior material model. RIS is based on the fact that cracks in orthotropic materials generally propagate along the fibers in the isotropic matrix media regardless of initial crack-fiber orientation. According to this fact, RIS offers to employ an isotropic stress field around the crack tip with defined stress reduction coefficients as fiber effects. This criterion is applicable for two cases wherein crack is placed both along and across the fibers. A comparison between available experimental data for two wood species and the results of the proposed criterion shows that this criterion can accurately predict both crack initiation and crack propagation direction and is in full compliance with the fracture nature of composite materials.